Species-specific and altitude-related variations in stomatal features of Berberis lycium Royle and B. parkeriana C.K. Schneid. Issue 1 (2nd January 2022) - Rahman, Inayat Ur; Afzal, Aftab; Calixto, Eduardo S.; Iqbal, Zafar; Abdalla, Mohnad; Alsamadany, Hameed; Parvez, Rainaz; Romman, Muhammad; Ali, Niaz; Sakhi, Shazia; Shah, Muzammil
ABSTRACT: Epidermal micro-morphological investigations have drawn the consideration of many researchers because of their taxonomic usefulness, but their relationship with environment is not completely known. Keeping this in view, quantitative leaf epidermal features (number of epidermal cells and stomata, and stomata length and width) were examined in the species Berberis lycium Royle and B. parkeriana C.K. Schneid along an altitudinal gradient at three different altitudes in Manoor Valley (Himalaya), Pakistan. A significant variability was found in the size and type of epidermal cells and stomata on both sides of the understory plants leaves. Berberis parkeriana had two types of stomata (anomocytic, and anisocytic) while Berberis lycium possesses a single type of stomata (paracytic). Furthermore, both species had stomata on the abaxial surface only. Berberis parkeriana had higher values of all parameters analyzed; the number of epidermal cells and stomata increased with increasing altitude while the length and width of stomata decreased with increasing altitude. This approach proved extremely valuable for the assessment of environmental impacts on the adaptive potential of plants and subsequent eco-physiological changes.